The bioelectrical impedance analysis (BIA) international database: aims, scope, and call for data - Silva, Analiza M.; Campa, Francesco; Stagi, Silvia; Gobbo, Luís A. [UNESP]; Buffa, Roberto; Toselli, Stefania; Silva, Diego Augusto Santos; Gonçalves, Ezequiel M.; Langer, Raquel D.; Guerra-Júnior, Gil; Machado, Dalmo R. L.; Kondo, Emi; et al. (Springer Nature, 2023)
Background: Bioelectrical impedance analysis (BIA) is a technique widely used for estimating body composition and health-related parameters. The technology is relatively simple, quick, and non-invasive, and is currently used globally in diverse settings, including private clinicians’ offices, sports and health clubs, and hospitals, and across a spectrum of age, body weight, and disease states. BIA parameters can be used to estimate body composition (fat, fat-free mass, total-body water and its compartments). Moreover, raw measurements including resistance, reactance, phase angle, and impedance vector length can also be used to track health-related markers, including hydration and malnutrition, and disease-prognostic, athletic and general health status. Body composition shows profound variability in association with age, sex, race and ethnicity, geographic ancestry, lifestyle, and health status. To advance understanding of this variability, we propose to develop a large and diverse multi-country dataset of BIA raw measures and derived body components. The aim of this paper is to describe the ‘BIA International Database’ project and encourage researchers to join the consortium. Methods: The Exercise and Health Laboratory of the Faculty of Human Kinetics, University of Lisbon has agreed to host the database using an online portal. At present, the database contains 277,922 measures from individuals ranging from 11 months to 102 years, along with additional data on these participants. Conclusion: The BIA International Database represents a key resource for research on body composition.